Optimalisasi Desa Wisata Ketapanrame sebagai Desa Wisata Pancasila melalui Penguatan Toleransi, Literasi Kebangsaan, dan Pemberdayaan Pemuda - Rojil Nugroho Bayu Aji; Mutimmatul Faidah; Mi’rojul Huda; Wiryo Nuryono; Diana Rahmasari; Nanda Audia Vrisaba; Aghus Sifaq (ABISATYA : Journal of Community Engagement, 2026)
This article reports a community service program conducted in Ketapanrame Tourism Village, Trawas District, Mojokerto Regency, focusing on the optimization of the village as an educational tourism space rooted in Pancasila values. The program responded to two interrelated needs: strengthening active tolerance amid social diversity and creating additional tourism value beyond natural attractions. The method consisted of situation analysis, problem identification, program socialization, coordination with village stakeholders and youth organizations, training, mentoring, focus group discussion, and participatory evaluation. The participants included youth, Karang Taruna members, village officials, and community leaders. The results indicate stronger youth awareness of mutual cooperation, civic literacy, moderation, digital promotion, and community-based tourism management. The activity also produced an initial concept for an educational tourism product, namely a civic literacy corner or nationalism cafe, to introduce Pancasila values, cultural diversity, and drug-free village awareness. The article argues that a Pancasila tourism village can serve as a community service model that integrates economic empowerment, character education, cultural preservation, and sustainable tourism. The results demonstrated two key outcomes: (1) enhanced participants' capacity in Pancasila values, active tolerance, civic literacy, digital promotion, and community-based tourism management; and (2) the development of a Pancasila-based educational tourism model, including a prototype Civic Literacy Corner, that integrates economic empowerment, character education, cultural preservation, and sustainable tourism.